Personalized stratification of hospitalization risk amidst COVID-19: A machine learning approach. Issue 3 (September 2021) - Lam, Carson; Calvert, Jacob; Siefkas, Anna; Barnes, Gina; Pellegrini, Emily; Green-Saxena, Abigail; Hoffman, Jana; Mao, Qingqing; Das, Ritankar
Highlights: A machine learning algorithm was able to predict severe response to COVID-19. This algorithm may help guide stay at home decisions and vaccine distribution. Machine learning may complement public policy in future infectious disease outbreaks. Abstract: Objective: In the wake of COVID-19, the United States (U.S.) developed a three stage plan to outline the parameters to determine when states may reopen businesses and ease travel restrictions. The guidelines also identify subpopulations of Americans deemed to be at high risk for severe disease should they contract COVID-19. These guidelines were based on population level demographics, rather than individual-level risk factors. As such, they may misidentify individuals at high risk for severe illness, and may therefore be of limited use in decisions surrounding resource allocation to vulnerable populations. The objective of this study was to evaluate a machine learning algorithm for prediction of serious illness due to COVID-19 using inpatient data collected from electronic health records. Methods: The algorithm was trained to identify patients for whom a diagnosis of COVID-19 was likely to result in hospitalization, and compared against four U.S. policy-based criteria: age over 65; having a serious underlying health condition; age over 65 or having a serious underlying health condition; and age over 65 and having a serious underlying health condition . Results: This algorithm identified 80% of patients at risk for hospitalization due to COVID-19, versus 62% identified by government guidelines. The algorithm also achieved a high specificity of 95%, outperforming government guidelines. Conclusions: This algorithm may identify individuals likely to require hospitalization should they contract COVID-19. This information may be useful to guide vaccine distribution, anticipate hospital resource needs, and assist health care policymakers to make care decisions in a more principled manner.